Reviews. (1st June 2019) - Dean, Levi; Daniels, Mikayla; Shahin, Yasser O.; Ho, Ilona Rossman
Television Antiheroines: Women Behaving Badly in Crime and Prison Drama, Milly Buonanno (2017) Bristol: Intellect, 285 pp., ISBN-13 978-1-78320-760-2, p/bk, 45kThe Girl Who Knew Too Much: Shadow of a Doubt (1943), Elaine Lennon (2016) Seattle: Amazon Digital Services LLC, 132 pp., ASIN: B01KTWF08U, e-Book, 3.99Writing for the Screen, Anna Weinstein (ed.) (2017) New York: Routledge, 254 pp., ISBN 978-1-13894-511-1, p/bk, 32.95; ISBN 978-1-31567-157-4, e-Book, 31.30The Heroine's Journey: Woman's Quest For Wholeness, Maureen Murdock (1990) Boulder, CO: Shambhala Publications, 232 pp., ISBN 978-0-87773-485-7, p/bk, 18.95; ISBN 978-0-81356-342-8, e-Book, 10.98